PENGARUH PENERAPAN METODE TIME GAMES TOURNAMENT (TGT) TERHADAP PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA MATERI INFAK DAN SEDEKAH DI KELAS V SD IT ULUL ALBAB JATI AGUNG LAMPUNG SELATAN - Linda Kartika; Arizal Eka Putra; Muhammad Sholihin (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2024)
The purpose of this research is to investigate the influence of the Time Games Tournament (TGT) method on improving students' learning outcomes and their response towards the TGT method. The methodology employed in this study is a quantitative true experimental design, utilizing data collection techniques such as pre-tests and post-tests, as well as a student response questionnaire. Sample selection was conducted using random sampling techniques, with data analysis including Shapiro-Wilk normality tests, hypothesis testing using paired t-tests, and N-Gain analysis. The results of the study indicate that the TGT method significantly enhances students' learning outcomes, as evidenced by the normal distribution of the data. The paired sample t-test yielded a significance value of 0.000 < 0.05, indicating a substantial impact of the TGT method on students' learning outcomes. Additionally, the N-Gain results showed a mean value of 57.6%, suggesting a satisfactory level of effectiveness for instructional purposes. Regarding students' responses to the TGT method, 83% expressed their interest, stating they are